A belt transect setting strategy for mark-recapture experiments to evaluate the 1D diffusion coefficient of beached litter in the cross-shore direction. Issue 1 (15th August 2016) - Hinata, Hirofumi; Kataoka, Tomoya
Abstract: We propose a belt transect setting strategy for mark-recapture experiments (MREs) to evaluate the time-independent 1D diffusion coefficient (〈 D p 0 〉) of marine litter in the cross-shore direction that determines the backwashing flux of the litter, based on two-year MREs for plastic floats (PFs) on Wadahama Beach, Nii-jima Island, Japan. When the alongshore width of the belt transect ( L t ) was of the order of, or longer than, the length scale of wave-induced nearshore current circulation ( L c ), the PFs were rarely transported alongshore across the selected transects prior to being backwashed offshore. Thus, the transect residence time became longer and showed a much weaker dependence on the transect position, in contrast to when L t was even shorter than L c . We therefore obtained the diffusion coefficients close to the value of (〈 D p 0 〉) when we set L t to the order of, or longer than, L c . Highlights: A transect setting strategy for mark-recapture experiments is proposed. The transect width is determined according to its relative position to nearshore currents. The strategy could be applicable to beaches with clear nearshore current circulation.